Offensive patterns analysis of Thai nation team in Volleyball Women's Nations League 2022 - Luangtrongkit, S.; Kongtongkum, P.; Rangubhet, K. R. (American Journal of Sports Science, 2024)
Effective offensive patterns are crucial for volleyball athletes, enabling quick and forceful attacks to strategically place the ball and impact the game. This study aimed to analyze the offensive strategies and outcomes of the Thai national team during the 2022 Women's Volleyball Nations League (VNL), comparing them with the opposing teams. Using a specific match model from the 13 matches and 51 sets held between May 31 and July 14, 2022, a total of 3,151 attack results were examined. Results were reported through means, standard deviations, percentages, and independent sample t-test statistical analysis for inter-group differences. The findings revealed that the Thai team predominantly utilized the curve ball spike (C) as the most aggressive offensive pattern (10.31±3.43), constituting 37.44% per match. The team's offensive performance showed a high score for successful attacks (ACE) at 35.08±10.75, equivalent to 28.79% per match. Comparative analysis indicated statistically significant differences in three offensive patterns at a 0.05 significance level. Notably, the Thai team excelled in the 3-meter ball spike (3M) at 24.38±8.00 (20.01% per match), fast spike (A) at 10.31±3.43 (8.46% per match), and dummy (X) at 6.23±3.81 (5.11% per match). However, there was no statistical difference in attack outcomes between the Thai team and the opponents. The Thai team's preference for the curve ball spike (C) constituted 37.44% per match, with a corresponding 28.79% success rate in attack scores (ACE). Notably, the 3M, A, and X offensive patterns exhibited significant differences between the Thai team and their opponents, while attack results showed no statistical variance.